The Beauty of Words in Maher Zain’s Selected Song Lyrics: A Study of Connotative Meaning - Dwi Utari Novianingsih; Firqo Amelia; Nine Febrie Novitasari (Universitas Muhammadiyah Jember, 2022)
There were so many connotative meaning could be found in Maher Zain’s song lyrics. This research gained the data through identifying the words or phrases on the lyrics in six Maher Zain’s songs and were analyzed based on Leech’s theory. The data were analyzed qualitatively, while the techniques of data collection are done by downloading the song and the lyrics, listening the song, reading the lyrics and watching the videos. Then, reducing the data, displaying the data, verifying the data and making the conclusion were done in analyzing the data. The result of the study described words/phrases containing types of connotative meaning. There were twenty-four data found in this research; sixteen data contained positive connotations, four data contained neutral connotations, and four data contained negative connotations. The researchers expected the next researchers to study the types of connotative meaning in other songs from Maher Zain in this album. The researchers also expected the next researchers to identify the types of connotations by using different relevant theory.